INavigS: uma infraestrutura de software ciente de contexto para navegação indoor - MEDEIROS, Allinger Lima (2018)
Context-aware computing is a research area of ubiquitous computing that aims to provide services and/or information without taking the user’s focus away from the current task. In turn, location-based services are categorized as a special type of context-aware applications, where localization assumes a primary role. Because of the evolution of positioning technologies and the fact that people spend most of their time in the indoor environment, the demand for indoor location-based services keeps growing. However, the development of these applications involves overcoming several challenges. In particular, for applications using indoor navigation services, one of the most important categories, the challenges include: obtaining user location and orientation, representing indoor space, generation custom routes, generation of instructions along the route, power management, and non-existence of APIs. In view of these challenges and in order to reduce the effort required for the development of these applications, this work proposes a context-sensitive and mobile-supported software infrastructure that provides transparent indoor positioning and navigation services.